The adventure zone. [1] : Here there be gerblins - McElroy, Clint, 1955-; McElroy, Clint, 1955-; Pietsch, Carey (First Second, 2018)
"Join Taako the elf wizard, Merle the dwarf cleric, and Magnus the human warrior for an adventure they are poorly equipped to handle AT BEST, guided ("guided") by their snarky DM, in a graphic novel that, like the smash-hit podcast it's based on, will tickle your funny bone, tug your heartstrings, and probably pants you if you give it half a chance." --